2017
DOI: 10.1016/j.afos.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Antiosteoporotic activity of Salvadora persica sticks extract in an estrogen deficient model of osteoporosis

Abstract: ObjectivesThe effect of Salvadora persica sticks on prevention of tooth decay is well established, but the effect of S. persica stick extract (SPE) on the prevention/treatment of osteoporosis has not been studied. The purpose of this study is to provide baseline information of the effectiveness of SPE on ovariectomized (OVX) rat model of osteoporosis.MethodsSPE was administered at 50, 150, and 300 mg/d orally to OVX rats for 16 weeks. Serum osteocalcin, alkaline phosphatase, calcium, and phosphorus, and urinar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…One kg of SP roots was cut into small pieces, air dried, and ground into fine powder and then extracted in distilled water for 48 h at 25°C. After centrifugation at 1435 ×g for 15 min, the resulting supernatants were filtered through Whatman number 1 filter paper and the filtrates were concentrated using a rotary evaporator at 40°C [ 21 ]. The obtained fine extract powder was subdivided into small portions in brown bottles and freshly prepared before supplementation to rats.…”
Section: Methodsmentioning
confidence: 99%
“…One kg of SP roots was cut into small pieces, air dried, and ground into fine powder and then extracted in distilled water for 48 h at 25°C. After centrifugation at 1435 ×g for 15 min, the resulting supernatants were filtered through Whatman number 1 filter paper and the filtrates were concentrated using a rotary evaporator at 40°C [ 21 ]. The obtained fine extract powder was subdivided into small portions in brown bottles and freshly prepared before supplementation to rats.…”
Section: Methodsmentioning
confidence: 99%
“…[31,120,121]. Among these studies, SP demonstrated a variety of effects that may influence periodontal therapy and play a role in improved regeneration and healing [51,62,67,122,123]. As elucidated in the studies [67], SP could activate transforming growth factor-β1 expression, promoting regenerative and stem cell functions,…”
Section: Regenerative and Stem Cell Modulationmentioning
confidence: 99%
“…[ 31 , 120 , 121 ]. Among these studies, SP demonstrated a variety of effects that may influence periodontal therapy and play a role in improved regeneration and healing [ 51 , 62 , 67 , 122 , 123 ]. As elucidated in the studies [ 67 ], SP could activate transforming growth factor-β1 expression, promoting regenerative and stem cell functions, including self-renewal and differentiation, adhesion, proliferation and migration, angiogenesis, as well as production of extracellular matrix components [ 67 , 124 ].…”
Section: Modes Of Action Of Salvadora Persica As Potential Adjuncts During Periodontal Therapy and In Periodontitis-asmentioning
confidence: 99%
“…S. persica stick extract efficacy in an ovary-ectomized rat model of osteoporosis was investigated by ( Fouda and Youssef, 2017 ) . The extract was taken p.o., at doses of 50, 150, and 300 mg/kg, dissolved in of distilled water to ovary-ectomized female Sprague–Dawley rats every morning for 16 weeks.…”
Section: Health Benefits Of the Plant And Its Extractsmentioning
confidence: 99%